ANALISIS KINERJA PERUSAHAAN SEBELUM DAN SESUDAH MERGER - APRILIA SARI, YENI (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this study was to determine differences in the debt to equity ratio, return on equity, net profit margin, return on asset, and earning per share in the performance of companies that merged in Indonesia. The objects used in this study is a company that merged listed in Indonesia Stock Exchange in 2012. The sample in this study amounted to 6 companies by using purposive sampling method. This study uses comparative research and data used secondary data. The method of analysis used is paired samples t-test. The results showed that the variable debt to equity ratio and return on asset there are differences in performance of the company before and after the merger while the variable net profit margin, return on equity and earning per share performance of the company there is no difference before and after the merger. Keywords: Merger, debt ratio, profitability ratio, paired sample t-test